Clinical efficacy of 0.1% cyclosporine A in dry eye patients with inadequate responses to 0.05% cyclosporine A: a switching, prospective, open-label, multicenter study - Sook Hyun Yoon; Eun Chul Kim; In-Cheon You; Chul Young Choi; Jae Yong Kim; Jong Suk Song; Joon Young Hyon; Hong Kyun Kim; Kyoung Yul Seo (BMC Ophthalmology)
Abstract Purpose To assess the clinical efficacy of 0.1% cyclosporine A (CsA) in dry eye patients who have shown inadequate responses to previous treatment with 0.05% CsA. Design This study was designed as a switching, prospective, multicenter, 12-week, open-label study. Methods Patients with dry eye disease (DED), who experienced inadequate responses to at least 3 months of treatment with 0.05% cyclosporine, were enrolled in this study. Clinical evaluations included the National Eye Institute (NEI) corneal and conjunctival staining scores, tear film break-up time (TF-BUT), Symptom Assessment in Dry Eye (SANDE), ocular discomfort scale (ODS), and tear volume. These parameters were assessed at baseline, and again at 4, 8, and 12 weeks after switching to 0.1% CsA. Results Ninety-one patients were enrolled in the study, and 70 patients completed the trial. Statistical analysis was performed on the full analysis set (FAS) using the Markov Chain Monte Carlo (MCMC) method to account for missing data. After switching to 0.1% CsA, subjective symptoms assessed by the Symptom Assessment in Dry Eye (SANDE) and Ocular Discomfort Scale (ODS) showed improvement (p < 0.0001). Objective signs of dry eye, including the National Eye Institute (NEI) score, tear film break-up time (TF-BUT), and tear volume also improved (p < 0.0001). Conclusions In patients with dry eye disease (DED) who exhibited inadequate responses to 0.05% cyclosporine A (CsA), switching to 0.1% CsA resulted in significant improvements in both subjective symptoms and objective clinical signs. This finding suggests that higher concentrations of CsA may be more effective in treating individuals with moderate to severe DED.